Alu antisense RNA ameliorates methylglyoxal-induced human lens epithelial cell apoptosis by enhancing antioxidant defense - Wu, Pei-Yuan; Wu, Chong-Guang; Wang, Xiao-Die; Liu, Xin; Song, Zhi-Xue; Khan, Murad; Shah, Suleman; Du, Ying-Hua; Wang, Xiu-Fang; Yan, Li-Fang (International journal of ophthalmology, 2023)
AIM: To determine whether an antisense RNA corresponding to the human Alu transposable element (Aluas RNA) can protect human lens epithelial cells (HLECs) from methylglyoxal-induced apoptosis. METHODS: Cell counting kit-8 (CCK-8) and 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays were used to assess HLEC viability. HLEC viability/death was detected using a Calcein-AM/PI double staining kit; the annexin V-FITC method was used to detect HLEC apoptosis. The cytosolic reactive oxygen species (ROS) levels in HLECs were determined using a reactive species assay kit. The levels of malondialdehyde (MDA) and the antioxidant activities of total-superoxide dismutase (T-SOD) and glutathione peroxidase (GSH-Px) were assessed in HLECs using their respective kits. RT-qPCR and Western blotting were used to measure mRNA and protein expression levels of the genes. RESULTS: Aluas RNA rescued methylglyoxal-induced apoptosis in HLECs and ameliorated both the methylglyoxal-induced decrease in Bcl-2 mRNA and the methylglyoxal-induced increase in Bax mRNA. In addition, Aluas RNA inhibited the methylglyoxal-induced increase in Alu sense RNA expression. Aluas RNA inhibited the production of ROS induced by methylglyoxal, restored T-SOD and GSH-Px activity, and moderated the increase in MDA content after treatment with methylglyoxal. Aluas RNA significantly restored the methylglyoxal-induced down-regulation of Nrf2 gene and antioxidant defense genes, including glutathione peroxidase, heme oxygenase 1, γ-glutamylcysteine synthetase and quinone oxidoreductase 1. Aluas RNA ameliorated methylglyoxal-induced increases of the mRNA and protein expression of Keap1 that is the negative regulator of Nrf2. CONCLUSION: Aluas RNA reduces apoptosis induced by methylglyoxal by enhancing antioxidant defense.